MILLENNIAL LEVEL OF AWARENESS OF LANGUAGE POLICY IN INDONESIA - Nuraini, Latifah; Pratama, Josua Ega Putra; Fawwaaz, Kevin Naufal (ISLLAC : Journal of Intensive Studies on Language, Literature, Art, and Culture, 2023)
This article discusses the level of the millennial about language policy. The millennials are living in a new period of time especially in Indonesia. As a national language, Indonesian language surely can't be separated from the policy of the Indonesian language. It was proclaimed in the youth pledge that the Indonesian language is a language that makes Indonesia one unity. The usage of the Indonesian language by the millennials through the time, there are also regional languages that are used as well. But lately, the use of good Indonesian language is threatened by foreign language use. Marked by this lately popular mixing of Indonesia and English language as a trend on the internet.